Serum zonulin level in autistic children and its relation to severity of symptoms a case-control study - Hassan Mohammed Sonbol; Alaa Salah Abdelmawgoud; Nora Marzouk El-kady; Eman Sameh Abdelhay; Hosam Eldin Abdel Tawab (Scientific Reports)
Abstract Evidence suggests a possible link between Autism spectrum disorder and gut permeability, specifically as indicated by serum zonulin levels. However, limited studies examine this connection to symptom severity, especially in Egypt. Assessing serum zonulin level in children with autism and its relation to the severity of symptoms. In Mansoura University Hospital’s pediatric psychiatry outpatient clinics, case-control research was carried out with children with Autism diagnoses and age- and gender-matched typically developing controls. The Childhood Autism Rating Scale was used to gauge the severity of the symptoms, and the Enzyme-Linked Immunosorbent Assay (ELISA) was used to detect serum zonulin levels. Serum zonulin levels were considerably higher in children with Autism than in the control group (p < 0.05). Additionally, there was a positive correlation between higher zonulin levels and the degree of autism symptoms as determined by CARS scores (r = X, p < 0.05). Children with severe Autism had the highest zonulin levels, according to subgroup analysis, which suggests a possible connection between gut permeability and the intensity of symptoms. This study emphasizes how serum zonulin may serve as a biomarker for intestinal permeability in kids with Autism and how it may be related to the intensity of symptoms. These results highlight the need for more investigation into the gut-brain axis as a potential therapeutic target for Autism. Addressing gut permeability may provide new ways to lessen the intensity of symptoms and enhance results for children with Autism.